THE ROLE OF THE CONTEXT OF THE FASHION PATTERN IN THE LEARNING OPERATION OF REAL NUMBERS - N Herawati; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to determine the role of the context of the fashion pattern in the learning operations of real numbers. In this lesson, learners are expected to be able to solve the problem of operation of real numbers in context. The method used in this research is the method of design research with the subjects of research students class X in SMK Negeri 2 Prabumulih, South Sumatera. This research develops learning result of real number operation by showing activity, procedure and strategies used by learners to solve the problem of operation of real number. The Indonesian realistic mathematics education approach is used in this study because it is in accordance with the context used. The results of this study show that the activity of making clothing patterns can improve the understanding of learners in understanding the operation of real numbers.